New genus of psychodinae (Diptera, psychodidae) from Argentina - Omad, Guillermo Hugo (2015)
Adults (male and female) and pupae of Chuspilepia saltenia gen. nov., sp. nov. were collected in tree holes in the Yungas rainforest, near San Ramón de la Nueva Orán city, Salta province, Argentina. It was not possible to place this new species in any known genera using the available keys and published descriptions, thus a new genus is proposed for the Neotropical region of Argentina.